Allelopathic Effects of Kyllinga brevifolia, Eleusine indica, and Sphagneticola trilobata on Lettuce (Lactuca sativa) - Tan Dang; Irawati Chaniago; Aprizal Zainal (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Weeds are a significant constraint to crop production as they compete for vital resources and release allelochemicals that may hinder the growth of surrounding plants. This study investigated the allelopathic effects of plant litter from Kyllinga brevifolia, Eleusine indica, and Sphagneticola trilobata on the germination and early development of Lactuca sativa. Two bioassays were conducted: a sandwich method in the laboratory and a pot experiment in a greenhouse. Dried weed residues were applied at concentrations of 1%, 2%, 3%, and 4% to evaluate their impact on seed germination, root and shoot elongation, and biomass accumulation in lettuce. The results showed that all three species inhibited seed germination and seedling growth in a concentration-dependent manner. In the sandwich assay, germination rates at 4% residue concentration declined to 58.89% (K. brevifolia), 76.67% (E. indica), and 46.67% (S. trilobata), compared to 96.67% in the control. The strongest inhibition of radicle growth was observed in K. brevifolia (91.60%). In the pot experiment, both K. brevifolia and S. trilobata consistently reduced all measured growth parameters. At 4%, shoot length declined to 9.18 mm and 5.42 mm, and dry shoot weight decreased to 2.90 mg and 3.09 mg, respectively. In contrast, E. indica slightly increased shoot biomass at moderate concentrations, suggesting a potential stimulatory effect. These findings demonstrate that residues from these weeds possess strong allelopathic potential and could be explored as natural agents for environmentally friendly weed management.